2018
DOI: 10.1248/bpb.b18-00029
|View full text |Cite
|
Sign up to set email alerts
|

Essential and Non-essential Elements in Scalp Hair of Diabetics: Correlations with Glycated Hemoglobin (HbA1c)

Abstract: Essential elements (Ca, Mg, Zn, Cu, Fe, Cr, Mn and V) and non-essential elements (As, Cd, Hg and Pb) were measured in scalp hair samples of 45 diabetic subjects and 59 control subjects in Japan using inductively coupled plasma mass spectrometry. All diabetic subjects took insulin and/or antidiabetic agents, with glycated hemoglobin (HbA1c) ranging between 6.2 and 14.4%. The levels of Zn, Cu and Cr in the diabetic subjects (HbA1c>7) were significantly lower than those in the control subjects (p<0.05), and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…Some included studies reported different effect sizes based on their studied subgroups; for these studies, we extracted and analyzed all suitable effect sizes. Of the included studies, data on Hg levels in T2DM patients vs. healthy controls were reported in 10 studies with 15 effect sizes [ 14 16 , 19 , 32 , 33 , 40 42 , 44 ], and 11 studies (3 prospective cohorts and 8 case-control) with 17 effect sizes [ 15 , 18 , 28 , 29 , 32 , 34 36 , 42 44 ] reported risk estimates for the association between Hg exposure and the risk of T2DM. All studies reporting risk estimates for T2DM adjusted the analysis for the potential confounders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some included studies reported different effect sizes based on their studied subgroups; for these studies, we extracted and analyzed all suitable effect sizes. Of the included studies, data on Hg levels in T2DM patients vs. healthy controls were reported in 10 studies with 15 effect sizes [ 14 16 , 19 , 32 , 33 , 40 42 , 44 ], and 11 studies (3 prospective cohorts and 8 case-control) with 17 effect sizes [ 15 , 18 , 28 , 29 , 32 , 34 36 , 42 44 ] reported risk estimates for the association between Hg exposure and the risk of T2DM. All studies reporting risk estimates for T2DM adjusted the analysis for the potential confounders.…”
Section: Resultsmentioning
confidence: 99%
“…In the pooled analysis of all eligible studies, Hg levels were significantly higher in T2DM patients compared with non-T2DM controls (random effects, SMD = 1.07; 95% CI = 0.59 to 1.55, P ≤ 0.001) ( Figure 2 ), with a significant heterogeneity across studies (I2 = 96.1%; P =≤0.001). In the stratified analysis by type of sample, compared with healthy controls, Hg levels were also significantly higher in blood (7 studies [ 16 , 19 , 32 , 40 42 , 44 ], SMD = 0.64 μ g/L; 95% CI = 0.05 to 1.22, P =0.03) and hair (3 studies [ 14 , 33 , 41 ], SMD = 3.15 μ g/L; 95% CI = 1.49 to 4.82, P ≤ 0.001) of patients with T2DM, but not in urine samples (based on 1 study [ 15 ]) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we opted for evaluating magnesium status by measuring the hair concentration. This approach has been used in various diseases [31], ranging from diabetes [32] to autoimmune disorders, with evidence for its applicability in patients with psoriasis [33] and alopecia areata [34].…”
Section: Discussionmentioning
confidence: 99%
“…Considering these aspects, an alternative to be considered for evaluating trace elements status is measuring the hair concentration. The approach of the measurement of multiple elements in the scalp hair is being applied to several diseases [ 17 ], ranging from diabetes [ 18 ] to autoimmune disorders. There is evidence for the usefulness of trace element evaluation in patients with psoriasis [ 19 ] and alopecia areata [ 9 ].…”
Section: Discussionmentioning
confidence: 99%